Policy Networks: Actors, Interests, and Power Relations in the Jakarta Bay Reclamation Project - Rizki Hegia Sampurna; Chih-Chieh Chou (Universitas Muhammadiyah Tangerang, 2021)
This case study seeks to understand the policy-making of the Jakarta bay reclamation project through the analytical lens of the policy networks. It posits that different policy networks would possibly produce or condition different policy outcomes in the project. The study uses a qualitative secondary data analysis. The study found: First, policy changes in the project, from initiation to implementation and finally termination, might be explained through the formation and transformation of different types of policy networks. Overall, the networks were characterized by fluctuating interactions among actors and the persistent power struggle between economic, environmental, and societal interests. Second, the networks’ type changes were possible due to two factors: (1) the political context of the 2017 gubernatorial election; and (2) the influences of environmental and societal ideas. Studi kasus ini berupaya untuk memahami pembuatan kebijakan proyek reklamasi teluk Jakarta melalui lensa analitik policy networks. Studiiniberasumsi bahwa jenis policy networksyang berbeda mungkin akan menghasilkan atau mengkondisikan hasil kebijakan yang berbeda dalam proyektersebut. Hasil studi ini menemukanbeberapatemuan. Pertama, perubahan kebijakan dalam proyek, dari inisiasi hingga implementasi dan akhirnya penghentian, dapat dijelaskan melalui pembentukan dan transformasi berbagai jenis policy networks. Secara keseluruhan, networkstersebutditandai oleh interaksi yang berfluktuasi di antara para aktor dan perebutan kekuasaan yang terus-menerus antara kepentingan ekonomi dan lingkungan dan masyarakat. Kedua, perubahan jenis networks tersebut kemungkinan disebabkan oleh dua faktor: (1) konteks politik Pilgub 2017; dan (2) pengaruh gerakanpemikiran lingkungan dan sosial.